Economic barriers of African students arriving in the Czech Republic - Lovětínská, Ivana; Neugebauer, Jan; Vokoun, Marek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
International students coming to the Czech Republic for education, experience, and potential future employment opportunities encounter a variety of challenges. While each student's experience is unique, shaped by personal background, financial situation, chosen university, and community support, specific challenges are common to most students. The primary objective of this study is to identify and analyze the economic and social barriers faced by African students, particularly those from Nigeria. To establish a strong theoretical foundation, the PRISMA–PICOT approach was applied, followed by a qualitative research design. Semi-structured interviews were conducted to validate or challenge the theoretical assumptions. The study focuses on two key phases of the international student experience: pre-arrival and post-arrival. The findings indicate that the most significant barrier in the pre-arrival phase is the visa application process, which involves difficulties in securing embassy appointments and fulfilling complex administrative requirements. In the post-arrival phase, financial insecurity becomes a major obstacle, as many students struggle to cover both initial and ongoing living expenses. The combination of these barriers creates a substantial burden, making the transition process more challenging and stressful for African students studying in the Czech Republic.

Studenci zagraniczni przyjeżdżający do Czech w celu zdobycia wykształcenia, doświadczenia i potencjalnych możliwości zatrudnienia napotykają na szereg wyzwań. Chociaż doświadczenia każdego studenta są wyjątkowe, kształtowane przez osobiste pochodzenie, sytuację finansową, wybraną uczelnię i wsparcie społeczności, specyficzne wyzwania są wspólne dla większości studentów. Głównym celem niniejszego badania jest identyfikacja i analiza barier ekonomicznych i społecznych, z jakimi borykają się studenci z Afryki, a zwłaszcza z Nigerii. Aby zbudować solidne podstawy teoretyczne, zastosowano metodę PRISMA–PICOT, a następnie jakościowy projekt badawczy. Przeprowadzono półustrukturyzowane wywiady w celu weryfikacji lub zakwestionowania założeń teoretycznych. Badanie koncentruje się na dwóch kluczowych fazach doświadczenia studentów zagranicznych: przed przyjazdem i po przyjeździe. Wyniki badań wskazują, że najważniejszą barierą w fazie przed przyjazdem jest proces ubiegania się o wizę, który wiąże się z trudnościami w uzyskaniu wizyt w ambasadzie i spełnieniu złożonych wymogów administracyjnych. W fazie po przyjeździe niepewność finansowa staje się główną przeszkodą, ponieważ wielu studentów ma trudności z pokryciem zarówno początkowych, jak i bieżących kosztów utrzymania. Połączenie tych barier stanowi poważne obciążenie, przez co proces adaptacji staje się trudniejszy i bardziej stresujący dla afrykańskich studentów studiujących w Czechach.
Ekonomiczne bariery przyjazdu afrykańskich studentów do Republiki Czeskiej
Keywords: abroad; African; Czech Republic; international; students; zagranica; afrykańscy; Republika Czeska; międzynarodowy; studenci